Terapi Komplementer Terhadap Kesehatan Mental Ibu Nifas Di Klinik Pratama Medical Center - Sthepani Sari Hidayat; Susanti Susanti (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The puerperium is an important period, as the risk of maternal and infant morbidity and mortality increases during this period. Hemorrhage is the leading cause of maternal death worldwide and most occur before 24 hours postpartum. Therefore, the birth attendant must ensure that the uterus contracts properly so that bleeding does not occur. The postpartum period is influenced by many factors, one of which is socio-cultural. Indonesia is a country consisting of various tribes and cultures that have their health traditions. Not all existing traditions have a bad effect on health but some have a positive impact on health. Efforts to assist and therapy to shape the coping skills of postpartum women are complementary therapy. Complementary therapy is a therapy that is used as a companion in conventional therapeutic efforts that a person has done. This type of research is descriptive by applying a case study approach. The implementation of this research was carried out at the Pratama Medical Center Clinic on Mrs. F by providing complementary health education education for mothers in the postpartum period.